Evaluation of Video Quality in Wireless Multimedia Sensor Networks - Mustafa Shakir; Obaid Ur Rehman; Zeeshan Abbas; Abdullah Masood; Wajeeha Shahid (Institute of Advanced Engineering and Science, 2016)
Simulating wireless sensor networks; there implementation and evaluation, require the use of a discrete event simulator. Omnet++ is quite a powerful simulator which supports concise and easy modeling of wired as well as wireless sensors environment. Scenarios involving multimedia transmissions with characteristics of video quality control and evaluation must be computed on the basis of Quality of Experience which relies on user’s perception to maintain the video quality. For the multimedia growth and awareness of future WMSNs, it is quite necessary that the performance should be tested for different types of radio models. So varying the radio parameters may allow for the optimization and improvement of the video quality. In this paper we have provided a test bench for the easy evaluation and optimization of the performance of WMSNs using different radio models. The performance is evaluated based on the QoE metrics; i.e. PSNR(Peak Signal-to-Noise ratio) and MoS(Mean Opinion Score), which depend on user’s perception to maintain the video quality.